(untitled) (Zoological Records and Reviews, 2022)
Estuaries represent among the most physically dynamic and biologically productive habitats on Earth, sustaining exceptional molluscan diversity owing to their transitional nature between freshwater and marine environments. Molluscs (Phylum Mollusca) are particularly well represented in estuarine systems, where bivalves, gastropods, and polyplacophorans occupy critical ecological roles as filter feeders, grazers, predators, and substrate engineers. This review synthesises published literature on molluscan diversity in estuarine ecosystems globally, with a focused analysis of European and South Asian estuaries, drawing on 214 primary studies published between 1985 and 2021. Global estimates suggest approximately 2,800 molluscan species are associated with estuarine habitats, of which approximately 680 are obligate estuarine specialists. Salinity gradient, sediment type, and tidal amplitude emerge as the dominant environmental predictors of molluscan species richness and community composition across estuarine systems. Invasive species, particularly Crassostrea gigas (Pacific oyster) and Potamocorbula amurensis (Asian clam), are documented to cause severe displacement of native molluscan assemblages in European and North American estuaries. Pollution, eutrophication, and sea-level rise are identified as major contemporary threats to estuarine molluscan diversity. Conservation and monitoring recommendations are discussed, with emphasis on integrating molluscan diversity assessments into estuarine management frameworks under the EU Water Framework Directive and equivalent regulatory instruments.